2023
DOI: 10.1037/vio0000414
|View full text |Cite
|
Sign up to set email alerts
|

The dark tetrad personality traits moderate the relationship between ideological passion and violent activism.

Abstract: Objective: This research examines the interface between ideological passion and the dark tetrad personality traits to predict violent (vs. peaceful) political activism. Meta-analytic research shows that ideological obsessive passion (OP) is one of the strongest psychological factors associated with violent activism. Here, we examine whether this relationship is magnified by the dark tetrad (i.e., Machiavellianism, narcissism, psychopathy, and sadism), which have often been associated with antisocial behavior. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 69 publications
(108 reference statements)
1
6
0
Order By: Relevance
“…At face value, these criteria match some of the OP scale items (e.g. "I have the impression that my [ideology] controls me", "This [ideology] is so exciting that I sometimes lose control over it", and research has shown that OP predicts distressing thoughts that radical individuals obsess over, such as collective or personal feelings of injustice, humiliation, or perceptions of harm done to the ingroup (Bélanger, 2021;Bélanger et al, 2022).…”
Section: Ocd: a Risk Factor For Ideological Obsession?mentioning
confidence: 96%
See 3 more Smart Citations
“…At face value, these criteria match some of the OP scale items (e.g. "I have the impression that my [ideology] controls me", "This [ideology] is so exciting that I sometimes lose control over it", and research has shown that OP predicts distressing thoughts that radical individuals obsess over, such as collective or personal feelings of injustice, humiliation, or perceptions of harm done to the ingroup (Bélanger, 2021;Bélanger et al, 2022).…”
Section: Ocd: a Risk Factor For Ideological Obsession?mentioning
confidence: 96%
“…Harmoniously passionate individuals view their activity as central to their sense of self, but it is unrelated to self-esteem contingencies (Mageau et al, 2011). Thus, HP is associated with greater flexibility in deciding when to engage in the activity (Vallerand et al, 2003;Bélanger et al, 2013a) and it does not interfere with other life domains such as friendships, professional obligations, or family life (Bélanger et al, 2022). OP, on the other hand, involves strong and uncontrollable urges to pursue one's ideology.…”
Section: Ideological Passion: a Cognitive-motivational Account Of Rad...mentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas HP is a consistent predictor of nonviolent activism (Bélanger, 2021; Gousse‐Lessard et al, 2013), OP has been shown to predict violent political intentions among a variety of groups ranging from Quebec nationalists (Rip et al, 2012), environmental activists (Gousse‐Lessard et al, 2013), US Republicans and Democrats (Bélanger, Schumpe, Nociti, et al, 2019), pro‐life activists (Bélanger et al, 2021), and Pakistani Muslims (Bélanger, Robbins, et al, 2020). OP also magnifies the relationship between sadism (a dark tetrad trait) and violent political intentions (see Bélanger, Adam‐Trioan, Quimpo, et al, 2022). OP was recently identified as one of the best predictors of radical intentions in a meta‐analysis including 37 putative risk factors (Wolfowicz et al, 2021).…”
Section: Ideological Passion: a Cognitive‐motivational Account Of Rad...mentioning
confidence: 99%